2019
DOI: 10.1080/19490976.2019.1580097
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gut microbiota composition and functions in patients with chronic alcohol overconsumption

Abstract: Excessive alcohol intake can alter the gut microbiota, which may underlie the pathophysiology of alcohol-related diseases. We examined gut microbiota composition and functions in patients with alcohol overconsumption for >10 years, compared to a control group of patients with a history of no or low alcohol intake. Faecal microbiota composition was assessed by 16S rRNA sequencing. Gut microbiota functions were evaluated by quantification of short-chain fatty acids (SCFAs) and predictive metagenome profiling (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 38 publications
9
136
0
2
Order By: Relevance
“…At the species level (Figure 3C), consistent with previous studies (Kolmeder et al, 2012; Zhang et al, 2017; Lin et al, 2018), we found that the main species was Faecalibacterium prausniizii (8-14%), except in S3, where Prevotella copri had an abundance of 14%. Previous studies showed that F. prausnitzii displayed beneficial effects against different alterations in the gastrointestinal tract (Bjørkhaug et al, 2019), and it had anti-inflammatory properties (Debyser et al, 2016). In the other hand, the role of P. copri in human health remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…At the species level (Figure 3C), consistent with previous studies (Kolmeder et al, 2012; Zhang et al, 2017; Lin et al, 2018), we found that the main species was Faecalibacterium prausniizii (8-14%), except in S3, where Prevotella copri had an abundance of 14%. Previous studies showed that F. prausnitzii displayed beneficial effects against different alterations in the gastrointestinal tract (Bjørkhaug et al, 2019), and it had anti-inflammatory properties (Debyser et al, 2016). In the other hand, the role of P. copri in human health remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…However, some particular drugs exert their therapeutic effects through selectively altering the structure of the gut microbiota, for example, increasing the abundance of Escherichia [46]. Sutterella is an opportunistic bacterium of the phylum Proteobacteria; human who have higher levels of the genera of Sutterella would have a lower concentration and percentage of butyric acid [47]. In https://doi.org/10.1371/journal.pone.0230200.g007…”
Section: Plos Onementioning
confidence: 99%
“…To summarize the relationship between proteins ispH and atoB and the genus Faecalibacterium: these two proteins were the most crucial to α-solanine synthesis in present study, and they were both assigned to this gut microbiome genus. In addition, previous studies reported that Faecalibacterium is a probiotic (Cao et al, 2014;Adamberg et al, 2015;Eppinga et al, 2016;Bjørkhaug et al, 2019).…”
Section: The Most Crucial Proteins and Their Assigned Generamentioning
confidence: 99%